Pembentukan Akuntabilitas Gereja Melalui Semangat Asas Kongregasional Baptis: Partisipatif Aktif Jemaat Dan Tanggung Jawab Kolektif - Timesa, Yosua Eka (Jurnal Sosial Teknologi, 2025)
This study examines the implications of the spirit of the Baptist congregational principle, especially the active participation of the congregation and collective responsibility, in the formation of church accountability in GBI Pengharapan Surabaya. GBI Pengharapan Surabaya was chosen as a case study because of the application of congregational principles in its distinctive organizational structure. A qualitative case study approach was used, involving in-depth interviews, participant observations, and document analysis as a method of data collection to gain a comprehensive understanding. The main findings show that the congregational principle encourages the creation of church accountability through the spirit of active participation of the congregation and collective responsibility, so that the mechanism of the church organization becomes more participatory. In addition, the implementation of Simple Church's church management system successfully integrates sacred and secular values in the ministry, strengthening members' awareness that matters considered spiritual and organizational practices are interconnected. This study makes a theoretical contribution by enriching the understanding of church accountability in the context of the Baptist church and congregational principles. The findings of this study are expected to help develop more effective and accountable ecclesiastical policies.